Economic Benefits of Waste Management Based on Cocoa Farming System in Rural Area: Evidence from East Kolaka District of Southeast Sulawesi Province - Witjaksono, Julian; Indrasti, Rita; Rawung, Jefny B Markus (International Journal of Sustainable Agricultural Research, 2020)
Indonesia is the three largest countries producing cocoa in the world. However, the productivity tends to be slow down, which cause concern income generation for smallholder farmers across the county. This study deals with the performance of diversification based on creating cocoa by product and waste management of livestock integrated farming in order to increasing household income due to low productivity. This research covers more than 120 household farmers as the respondent through the survey by using questionnaire in three districts population sample. The results of this study indicate that the response of farmers in this study location those are introduced technology components shows effective value. This shows a positive support for the results of this study. The results of the cost and feasibility analysis of the business of making solid organic fertilizers, processing cocoa beans and making bio-char or biological charcoal of cocoa pod show those businesses can be a pattern of diversification of farm household income in the small scale concept. The household scale model of this study development through the zero waste concepts applied at the study site is expected to be a recommendation for the local government in an effort to improve the welfare of cocoa farmer households in this region.